Planets, candidates, and binaries from the CoRoT/Exoplanet programme*: the CoRoT transit catalogue - Deleuil, Magali; Gandolfi, Davide (Arxiv, 2018)
We provide the catalogue of all transit-like features, including false alarms, detected by the CoRoT exoplanet teams in the 177 454 light curves of the mission. All these detections have been re-analysed with the same softwares so that to ensure their homogeneous analysis. Although the vetting process involves some human evaluation, it also involves a simple binary flag system over basic tests: detection significance, presence of a secondary, difference between odd and even depths, colour dependence, V-shape transit, and duration of the transit. We also gathered the information from the large accompanying ground-based programme carried out on the planet candidates and checked how useful the flag system could have been at the vetting stage of the candidates. In total, we identified and separated 824 false alarms of various kind, 2269 eclipsing binaries among which 616 are contact binaries and 1653 are detached ones, 37 planets and brown dwarfs, and 557 planet candidates. For the planet candidates, the catalogue gives not only their transit parameters but also the products of their light curve modelling, together with a summary of the outcome of follow-up observations when carried out and their current status. Among the planet candidates whose nature remains unresolved, we estimate that 8 +/- 3 planets are still to be identified. We derived planet and brown dwarf occurrences and confirm disagreements with Kepler estimates: small-size planets with orbital period less than ten days are underabundant by a factor of three in the CoRoT fields whereas giant planets are overabundant by a factor of two. These preliminary results would however deserve further investigations using the recently released CoRoT light curves that are corrected of the various instrumental effects and a homogeneous analysis of the stellar populations observed by the two missions.